1992
DOI: 10.1093/oxfordjournals.humrep.a137779
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of treatment subsequent to the elective cryopreservation of all embryos from women at risk of the ovarian hyperstimulation syndrome

Abstract: From 1st June 1989 to 31st May 1991, 78 women with a serum oestradiol level greater than 3500 pg/ml on the day of the ovulatory trigger, following pituitary suppression with buserelin and ovarian stimulation with human menopausal gonadotrophins (HMG), had all their embryos electively cryopreserved at the pronucleate stage to minimize the risk of developing ovarian hyperstimulation syndrome (OHS). Treatment with buserelin was continued in the luteal phase. A median of 19 oocytes (range 7-43) was obtained and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Although early OHSS associated with hCG administration may still occur (76)(77)(78)(79), it is the increase in endogenous hCG associated with pregnancy that is responsible for secondary exacerbation of early OHSS or the development of late OHSS, and these more serious forms of the condition can thus be avoided (77,80,81). Where OHSS does occur after cryopreservation, the severity and duration of the condition appear to be reduced (82).…”
Section: Cryopreservation Of All Embryosmentioning
confidence: 99%
“…Although early OHSS associated with hCG administration may still occur (76)(77)(78)(79), it is the increase in endogenous hCG associated with pregnancy that is responsible for secondary exacerbation of early OHSS or the development of late OHSS, and these more serious forms of the condition can thus be avoided (77,80,81). Where OHSS does occur after cryopreservation, the severity and duration of the condition appear to be reduced (82).…”
Section: Cryopreservation Of All Embryosmentioning
confidence: 99%
“…Systemic and ovarian-related inflammatory mediators such as cytokines (including interleukins 1, 2, 6, and 8 and www.elsevier.com/locate/rigapp Reviews in Gynaecological and Perinatal Practice 6 (2006) [26][27][28][29][30][31][32] tumour necrosis factor alpha (TNFa)), histamine, prostaglandins and vascular endothelial growth factor (VEGF) have been studied to establish their role in OHSS [4,5].…”
Section: Immune Systemmentioning
confidence: 99%
“…Avoiding fresh embryo transfer in patients at high risk of developing OHSS prevents the late onset of the syndrome by simply eliminating the rise of hCG associated with successful embryo implantation. Although several studies have indicated that cryopreservation of all embryos reduced the risk of OHSS while achieving acceptable pregnancy rates (9,19,20), a Cochrane review concluded, on the basis of two studies, that there was insufficient prospective evidence to conclude that cryopreservation prevented OHSS, compared with albumin administration or no cryopreservation (21).…”
mentioning
confidence: 99%